Men of our time [videorecording] Mussolini - Lagone, Patricia; Taylor A. J. P. (Heroes and tyrants of the twentieth century series, 1990)
Benito Mussolini was a ruler with no identity, a man who neither understood himself nor his country. Contains his theatrical personality from his egocentric oratory, his march on Rome, his private war with Adolf Hitler, and his crushing defeats on the battlefield.